Short-Term HMB Supplementation Reduces Muscle Damage after a Bout of Resistance Training in non-Athletic Females - Saiwan Sirwan Mohammed; Dara Latif Sayfaddin; Hiwa Ahmed Rahim; Dashni Anwer Kareem; Makwan Jabar Ali; Salah Mahmood Omar; Hassan Hashim Abdulla; Renas Abdullah Ali; Harem Abdalqadir Mohammed; Berivan Jalal Rashid (CV. FOUNDAE, 2022)
Starting or continuing physical activity, especially for non-athletes, can be a challenge due to muscle injuries caused by physical activity. Therefore, the present study aimed to investigate the short-term effect of beta-hydroxy beta-methyl butyrate (HMB) supplementation on muscle and liver damage caused by a period of resistance activity in non-athletic females. Among the volunteers, 16 female non-athletes with an average age of 21.75±1.18 years, a body mass index of 24.83±2.67 kg/m2, and a weight of 63.43±8.46 kg were randomly selected as a statistical sample. The subjects were randomly divided into two groups of eight people, HMB supplement and placebo. Daily and for six days, the subjects of the supplement group received 3 mg of beta-hydroxy beta-methyl butyrate powder. The placebo group received 3 grams of starch in tablet form. After six days of loading, the subjects performed a resistance activity session with an intensity of 75-80 percent 1RM. Blood samples were taken in five stages, including before supplementation, before training, immediately, 1 hour, and 24 hours after sports activity. To compare the results, a 5x2 analysis of variance test was used. The results showed that the consumption of HMB supplements significantly affected the serum levels of Creatine kinase (CK) and lactate dehydrogenase (LDH) enzymes in the blood and the amount of aspartate aminotransferase (AST) and alanine aminotransferase enzyme activity in the blood of intragroup interactions (p less than 0.05). On the other hand, there was no significant difference between the serum levels of CK enzyme and the activity of ALT and AST enzymes between the two supplement and placebo groups (p more than 0.05). There was no significant difference in the serum level of LDH enzyme between the two supplement and placebo groups (P less than 0.05). Although the results of the present study showed that consuming 3 grams of HMB supplement reduces the LDH response after resistance training, this supplement cannot be used as an independent factor for reducing muscle damage markers following intense physical activities. As a new achievement, it is recommended that HMB supplements be taken more cautiously to reduce indicators of muscle damage.